Transcranial Direct Current Stimulation and Cognition in Neuropsychiatric Disorders: Systematic Review of the Evidence and Future Directions. (June 2021) - Ciullo, Valentina; Spalletta, Gianfranco; Caltagirone, Carlo; Banaj, Nerisa; Vecchio, Daniela; Piras, Fabrizio; Piras, Federica
Transcranial direct current stimulation (tDCS) has been implemented in neuropsychiatric disorders characterized by cognitive impairment. However, methodological heterogeneity challenges conclusive remarks. Through a critical analysis of previous conflicting findings and in the light of current neurobiological models of pathophysiology, we qualitatively assessed the effects of tDCS in neuropsychiatric disorders that share neurobiological underpinnings, as to evaluate whether stimulation can improve cognitive deficits in patients' cohorts. We performed a systematic review of tDCS studies targeting cognitive functions in mental disorders and pathological cognitive aging. Data from 41 studies, comprising patients with diagnosis of mood disorders, schizophrenia-spectrum disorders, Alzheimer's disease (AD), and mild cognitive impairment (MCI), were included. Results indicate that tDCS has the capacity to enhance processing speed, working memory, and executive functions in patients with mood and schizophrenia-spectrum disorders. The evidence of a positive effect on general cognitive functioning and memory is either inconclusive in AD, or weak in MCI. Future directions are discussed for developing standardized stimulation protocols and for translating the technique therapeutic potential into effective clinical practice.